Effectiveness of Procedural Education in The Reduction of Hars Anxiety Scores in Pre-Surgical Patients - Rokhmatul Hikhmat; Muslimin; Herlinawati; Muhidin; Desi Arisandi (Kirana Publisher (KNPub), 2026)
This study aims to analyze the effectiveness of providing procedural education in reducing the Hamilton Anxiety Rating Scale (HARS) anxiety score in pre-surgical patients at Purwakarta Holistic Hospital. Anxiety is a systemic stress response that often arises due to uncertainty of information about the invasive procedures that patients will face. The research method uses a quantitative approach with a correlative descriptive design through a cross-sectional design. The study population involved all pre-operative patients in the study period with a total sampling technique of 30 respondents. The research instruments included a completeness questionnaire and a HARS scale observation sheet to measure 14 parameters of clinical manifestations of anxiety. Data analysis was carried out univariate and bivariate using the Chi-Square correlation test. The results showed that the majority of respondents had a secondary education background (53.3%) and received procedural information in the incomplete category (63.3%). The distribution of anxiety levels was dominated by the moderate category of 46.7%, where the most prominent clinical manifestations were palpitations, motor anxiety, and insomnia. The results of statistical tests proved that there was a significant relationship between the completeness of the procedural information provision and the reduction of the patient's anxiety score (p < 0.05). The study's conclusions confirm that comprehensive procedural education is effective as a therapeutic instrument to mitigate systemic stress responses and improve patients' adaptive coping before invasive measures. The research recommendations emphasize the importance of revitalizing the educational role of nurses through standard operating procedures that require pain management guidance to ensure hemodynamic stability and patient safety in the surgical unit.